Effect of number of hours and days of accelerometer use on physical activity estimates in adolescents - Arthur Oliveira Barbosa; Alcides Prazeres Filho; José Cazuza Farias Júnior (Revista Brasileira de Cineantropometria e Desempenho Humano)
The study analyzed the effect of number of hours and days of accelerometer use on estimates of physical activity (PA) time in adolescents. Cross-sectional study of 784 adolescents from 10 to 14 years old (53.9% girls). Overlapping 95% confidence intervals (95%CI) were used to compare mean light (LPA), moderate (MPA), vigorous (VPA) and moderate to vigorous (MVPA) physical activity times and prevalence of sufficient PA levels between different numbers of hours (?6, ?8 and ?10 hours/day) and days (?3, ?4, ?5 and 7 days of use). The criterions of ?6 hours/day with ?3, ?4, ?5 e 7 days and ?8 hour/day with ?3, ?4 e ?5 days of accelerometer use underestimated, in average, the LPA time in 23.1 and 12.6 min/day, respectively, compared ?10 hours/day. There were no significant differences in mean MPA, VPA and MVPA times and prevalence of sufficient PA levels between the number of hours and days of use analyzed. To produce accurate estimates of PA time in teenagers, ?3 days of accelerometer use was adopted for ?10 hours/day of LPA and ? 6 hours/day of MPA, VPA and MVPA.